Double reading of current chest CT examinations: Clinical importance of changes to radiology reports. Issue 1 (January 2016) - Lauritzen, Peter M.; Stavem, Knut; Andersen, Jack Gunnar; Stokke, Mali Victoria; Tennstrand, Anne Lise; Bjerke, Gisle; Hurlen, Petter; Sandbæk, Gunnar; Dahl, Fredrik A.; Gulbrandsen, Pål
Highlights: Double reading is used for quality assurance of radiology interpretation. We evaluated the clinical importance of changes to chest CT reports. Double reading resulted in clinically important changes to 9% of chest CT reports. 80% of clinically important changes implied increased severity of findings. Most critical and large report changes concerned cardiovascular issues or cancer. Abstract: Objectives: Misinterpretation of radiological examinations is an important contributing factor to diagnostic errors. Double reading reduces interpretation errors and increases sensitivity. Consultant radiologists in Norwegian hospitals submit 39% of computed tomography (CT) reports for quality assurance by double reading. Our objective was to estimate the proportion of radiology reports that were changed during double reading and to assess the potential clinical impact of these changes. Materials and methods: In this retrospective cross-sectional study we acquired preliminary and final reports from 1023 consecutive double read chest CT examinations conducted at five public hospitals. The preliminary and final reports were compared for changes in content. Three experienced pulmonologists independently rated the clinical importance of these changes. The severity of the radiological findings in clinically important changes was classified as increased, unchanged, or decreased. Results: Changes were classified as clinically important in 91 (9%) of 1023 reports. Of these: 3 were critical (demanding immediate action), 15 were major (implying a change in treatment) and 73 were intermediate (affecting subsequent investigations). More clinically important changes were made to urgent examinations and less to female first readers. Chest radiologist made more clinically important changes than other second readers. The severity of the radiological findings was increased in 73 (80%) of the clinically important changes. Conclusion: A 9% rate of clinically important changes made during double reading may justify quality assurance of radiological interpretation. Using expert second readers and targeting a selection of urgent cases prospectively may increase the yield of discrepant cases and reduce harm to patients.